Analysis of coastal vulnerability of Rangsang Island due to climate changes - Ahmad Nurhuda; M Mubarak; Sigit Sutikno (Journal of Degraded and Mining Lands Management, 2019)
Rangsang Island is home to more than 48,000 residents. Climate change has been a critical issue to the Island and threatened the existence of the inhabitants. This study is proposed to identify the zone of the coastal area of Rangsang Island which is vulnerable to climate change. By mapping coastal vulnerability index (CVI) of the island, it is expected to be a reference of local government in planning their spatial management. The method of this study was by a direct survey for collecting data of geomorphology, beach elevation, sea level rise, tidal fluctuation, significant wave height, and changes in the coastline. To determine CVI, each parameter is divided into 5 categories and given a value level: 1 for very not vulnerable, 2 for not vulnerable, 3 for moderate, 4 for vulnerable, and 5 for very vulnerable. The results show that most villages on the island are classified as highly vulnerable to climate change, namely 9 villages. Even 2 villages are threatened very high risk because the village has CVI more than 12.5. Only 6 villages whose territory has moderate vulnerability index. Vulnerability level of coastal Rangsang Island is strongly influenced by geomorphological variable and coastal elevation. In addition, the variable coastline changes and sea level rise also contributed to the vulnerability index of the Island.